Isometric Exercise Training and Arterial Hypertension: An Updated Review - Edwards, JJ; Coleman, DA; Ritti-Dias, RM; Farah, BQ; Stensel, DJ; Lucas, SJE; Millar, PJ; Gordon, BDH; Cornelissen, V; Smart, NA; Carlson, DJ; McGowan, C; et al. (Springer, 2024)
Hypertension is recognised as a leading attributable risk factor for cardiovascular disease and premature mortality. Global initiatives towards the prevention and treatment of arterial hypertension are centred around non-pharmacological lifestyle modification. Exercise recommendations differ between professional and scientific organisations, but are generally unanimous on the primary role of traditional aerobic and dynamic resistance exercise. In recent years, isometric exercise training (IET) has emerged as an effective novel exercise intervention with consistent evidence of reductions in blood pressure (BP) superior to that reported from traditional guideline-recommended exercise modes. Despite a wealth of emerging new data and endorsement by select governing bodies, IET remains underutilised and is not widely prescribed in clinical practice. This expert-informed review critically examines the role of IET as a potential adjuvant tool in the future clinical management of BP. We explore the efficacy, prescription protocols, evidence quality and certainty, acute cardiovascular stimulus, and physiological mechanisms underpinning its anti-hypertensive effects. We end the review with take-home suggestions regarding the direction of future IET research.